2020
DOI: 10.1111/jmi.12946
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge: the role of Atgolgin‐84A at the plant ER–Golgi interface

Abstract: The plant Golgi apparatus is responsible for the processing of proteins received from the endoplasmic reticulum (ER) and their distribution to multiple destinations within the cell. Golgi matrix components, such as golgins, have been identified and suggested to function as putative tethering factors to mediate the physical connections between Golgi bodies and the ER network. Golgins are proteins anchored to the Golgi membrane by the C-terminus either through transmembrane domains or interaction with small regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…We found that Golgi bodies are motile and associated with ER tubules (Figure 1A; Supplementary movie S1) or curved edges of cisternae (Figure 1B) or may be trapped within small lacunae in ER cisternae (Figure 1C). Although connections between ER and Golgi bodies have been described before (daSilva et al, 2004;Sparkes et al, 2009;Osterrieder et al, 2017;Vieira et al, 2020), our results indicate that we can visualize the spatial distribution of the ER and Golgi in live cells at a level of resolution that has not been reported before.…”
Section: High-resolution Imaging Of the Er-golgi Interface In Live Pl...mentioning
confidence: 49%
See 1 more Smart Citation
“…We found that Golgi bodies are motile and associated with ER tubules (Figure 1A; Supplementary movie S1) or curved edges of cisternae (Figure 1B) or may be trapped within small lacunae in ER cisternae (Figure 1C). Although connections between ER and Golgi bodies have been described before (daSilva et al, 2004;Sparkes et al, 2009;Osterrieder et al, 2017;Vieira et al, 2020), our results indicate that we can visualize the spatial distribution of the ER and Golgi in live cells at a level of resolution that has not been reported before.…”
Section: High-resolution Imaging Of the Er-golgi Interface In Live Pl...mentioning
confidence: 49%
“…Pre-cis-Golgi compartments have been previously suggested for proteins proposed to be involved in ER-Golgi tethering: AtGolgin-84A, which colocalizes with Sar1a (Vieira et al, 2020), as well as AtCASP (Latijnhouwers et al, 2007;Osterrieder et al, 2017) and the Arabidopsis ER-a-mannosidase I (MNS3; (Schoberer et al, 2019)). Our results support the existence of a pre-cis-Golgi compartment where COPII components accumulate rather than accumulating on the ER.…”
Section: Discussionmentioning
confidence: 99%
“…Golgi body distribution was assessed as in Renka 77 and Vieira et al 76 Briefly, images of Golgi body distribution were collected and cropped to the largest possible rectangle containing only cell area within the field of view. Using the ImageJ multi-point tool, the co-ordinates of each Golgi body were manually obtained.…”
Section: Golgi Body Distributionmentioning
confidence: 99%
“…Atp115/MAG4 locates at cis -Golgi and mediates the transport of storage protein precursors from the ER to the Golgi ( Takahashi et al, 2010 ). AtCASP and Atgolgin84 locates to the cis -Golgi and are implicated in tethering the Golgi to the ERES ( Latijnhouwers et al, 2007 ; Osterrieder et al, 2017 ; Vieira et al, 2020 ). So far, except for Atp115, no biological study of golgin on plant development has been conducted.…”
Section: Intra-golgi Transportmentioning
confidence: 99%